Pengembangan Video Animasi Toonly Pada Mata Kuliah Bunpo Shochukyu (Bab 44-46) - I Gusti Ayu Diah Anggreni Dewi; Kadek Eva Krishna Adnyani; Gede Satya Hermawan (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to: (1) develop a Toonly animation video suitable for the bunpo shochukyu course at the Japanese Language Education Study Program at Ganesha University of Education (UNDIKSHA); and (2) analyze the feasibility level of the Toonly animation video suitable for the bunpo shochukyu course at the Japanese Language Education Study Program at Ganesha University of Education (UNDIKSHA). This study uses the MDLC (Multimedia Development Life Cycle) development model modified by Binanto. The subjects of this study were grade 2 students at the UNDIKSHA Japanese Language Education Study Program. The data were analyzed qualitatively and quantitatively. Data was collected by conducting interviews and completing questionnaires. The results of this study are: (1) Three animation videos which are suitable video characteristics according to the Buncher (2) Based on expert judgment material, the animated video received an average rating of 54 (very good). According to the media expert's assessment, animated videos obtained an average rating of 57 (very good). Meanwhile, in the assessment of six actors, an average rating of 115.1 (very good) was obtained. Based on the results of the assessment, the three animation videos were declared suitable for use in the Bunpo Shochukyu course at the UNDIKSHA Japanese Language Education Study Program.